Noisy presences in contemporary European cinema: Paris est une fête: un film en 18 vagues - Talijan, E (Routledge, 2021)
This chapter argues that contemporary filmmakers have worked with noise in their approach to sound design to think about the intensified relations between bodies in global culture. Cinematic listening in European cinema is shaped by continual instances of overhearing as filmmakers reflect on contemporary issues of migration, borders, social inequality and so on; the act of viewing is stirred by noisy presences that redefine the boundaries of bodies, spaces and identities. The chapter discusses the political documentary Paris est une fete: un film en 18 vagues by the experimental film practitioner Sylvain George. Politics in Paris est une fete becomes a case of extending or restricting the limits of the body in public space, something which the film explores through noise. Noise becomes an aesthetic through which Paris est une fete communicates an insurrectionary energy that defies forms of containment, such as urban planning or policing.